(±)‐Hippolide J – A Pair of Unusual Antifungal Enantiomeric Sesterterpenoids from the Marine Sponge Hippospongia lachne. Issue 24 (26th June 2017) - Jiao, Wei‐Hua; Hong, Li‐Li; Sun, Jia‐Bao; Piao, Shu‐Juan; Chen, Guo‐Dong; Deng, Hai; Wang, Shu‐Ping; Yang, Fan; Lin, Hou‐Wen
Abstract : A pair of enantiomeric sesterterpenoids, (±)‐hippolide J (1a and1b ), were isolated from the marine sponge Hippospongia lachne collected from the South China Sea. The racemic mixture was resolved into a pair of enantiomers, (–)‐1a and (+)‐1b, by chiral HPLC separation. The structures of the enantiomers were determined through ESI‐HRMS and NMR spectroscopic analysis, and their absolute configurations were determined by comparison between the calculated and experimental electronic circular dichroism (ECD) spectra. Hippolide J (1 ) features an unusual bicyclo[4.2.0]octene core and contains three functional groups, namely, a hydroxymethyl group, an α, β‐unsaturated γ‐lactone fragment, and a characteristic prenyl side‐chain. The evaluation of the antifungal activity of (–)‐1a and (+)‐1b revealed that both show potent antifungal activity against three strains of hospital‐acquired pathogenic fungi, namely, Candida albicans SC5314, Candida glabrata 537, and Trichophyton rubrum Cmccftla, with MIC50 (minimum concentration to give 50 % inhibition) values of 0.125–0.25 µg/mL. Abstract : (±)‐Hippolide J (1 ), a pair of unusual enantiomeric sesterterpenoids, are isolated from the South China Sea marine sponge Hippospongia lachne . The racemic mixture is resolved into (–)‐1a and (+)‐1b by chiral HPLC. Both (–)‐1a and (+)‐1b showed potent antifungal activity against three strains of hospital‐acquired pathogenic fungi; therefore, they are promising new lead agents for antifungal therapy.